Fluorine in fragrances: exploring the difluoromethylene (CF 2 ) group as a conformational constraint in macrocyclic musk lactones - Corr, Michael J.; Cormanich, Rodrigo A.; von Hahmann, Cortney N.; Bühl, Michael; Cordes, David B.; Slawin, Alexandra M. Z.; O'Hagan, David (Organic & biomolecular chemistry, 2016)
The CF 2 group is incorporated into specific positions within the lactone ring of the natural musk lactone, (12 R )-(+)-12-methyl-13-tridecanolide, a constituent of Angelica root oil, Angelica archangelica L. The approach is taken as it was anticipated that CF 2 groups would dictate corner locations in the macrocycle and limit the conformational space available to the lactone. Three fluorine containing lactones are prepared by organic synthesis. One ( 8 ) has CF 2 groups located at the C-6 and C-9 positions, another ( 9 ) with CF 2 groups at the C-5 and C-9 positions, and a third ( 10 ) with a CF 2 group at C-8. Two of the fluorine containing lactones ( 8 and 10 ) were sufficiently crystalline to obtain X-ray crystal structures which revealed that the CF 2 groups do adopt corner locations. All three lactones were subject to computational analysis at the B3LYP-D3/6-311+G** level to assess the relative energies of different conformers. In all cases, the global minima and most of the lowest energy minima have squared/rectangular geometries and located the CF 2 groups at the corners. The lowest energy structures for 8 and 10 closely approximated the observed X-ray structures, suggesting good convergence of theory and experiment in determining relevant low energy conformations. All three compounds retained a pleasant odour suggesting the rings retained sufficient conformational flexibility to access relevant olfactory conformations.